Hypothalamic POMC or MC4R deficiency impairs counterregulatory responses to hypoglycemia in mice - Benjamin P. Tooke; Hui Yu; Jessica M. Adams; Graham L. Jones; Talisha Sutton-Kennedy; Lakshmi Mundada; Nathan R. Qi; Malcolm J. Low; Kavaljit H. Chhabra (Elsevier, 2019)
Objective: Life-threatening hypoglycemia is a major limiting factor in the management of diabetes. While it is known that counterregulatory responses to hypoglycemia are impaired in diabetes, molecular mechanisms underlying the reduced responses remain unclear. Given the established roles of the hypothalamic proopiomelanocortin (POMC)/melanocortin 4 receptor (MC4R) circuit in regulating sympathetic nervous system (SNS) activity and the SNS in stimulating counterregulatory responses to hypoglycemia, we hypothesized that hypothalamic POMC as well as MC4R, a receptor for POMC derived melanocyte stimulating hormones, is required for normal hypoglycemia counterregulation. Methods: To test the hypothesis, we induced hypoglycemia or glucopenia in separate cohorts of mice deficient in either POMC or MC4R in the arcuate nucleus (ARC) or the paraventricular nucleus of the hypothalamus (PVH), respectively, and measured their circulating counterregulatory hormones. In addition, we performed a hyperinsulinemic-hypoglycemic clamp study to further validate the function of MC4R in hypoglycemia counterregulation. We also measured Pomc and Mc4r mRNA levels in the ARC and PVH, respectively, in the streptozotocin-induced type 1 diabetes mouse model and non-obese diabetic (NOD) mice to delineate molecular mechanisms by which diabetes deteriorates the defense systems against hypoglycemia. Finally, we treated diabetic mice with the MC4R agonist MTII, administered stereotaxically into the PVH, to determine its potential for restoring the counterregulatory response to hypoglycemia in diabetes. Results: Stimulation of epinephrine and glucagon release in response to hypoglycemia or glucopenia was diminished in both POMC- and MC4R-deficient mice, relative to their littermate controls. Similarly, the counterregulatory response was impaired in association with decreased hypothalamic Pomc and Mc4r expression in the diabetic mice, a phenotype that was not reversed by insulin treatment which normalized glycemia. In contrast, infusion of an MC4R agonist in the PVH restored the counterregulatory response in diabetic mice. Conclusion: In conclusion, hypothalamic Pomc as well as Mc4r, both of which are reduced in type 1 diabetic mice, are required for normal counterregulatory responses to hypoglycemia. Therefore, enhancing MC4R function may improve hypoglycemia counterregulation in diabetes. Keywords: Hypothalamus, Pro-opiomelanocortin (POMC), Melanocortin 4 receptor (MC4R), Hypoglycemia counterregulation, Diabetes